THE DECLINE OF ISLAM AND WESTERN COLONIZATION OF THE ISLAMIC WORLD - Saipullah, Saipullah; Aditiya, A. Reza; Yanor, Yanor (Yayasan Maslahatul Ummah Ilal Jannah, 2023)
This research explains that Islamic civilization has experienced a period recorded in history as a period of decline, apart from its golden age. The results of the analysis of various literature sources resulted in the classification of the flow of events and cause-effect of the occurrence of the decline of Islam from various sides, which became elements of civilization as well as its decline. Along with the decline of Islamic civilization, on the contrary, Western civilization actually achieved its progress as a sustainable impact of the entry of the West into the Renaissance period. The progress achieved by the West provided opportunities for them to colonize the declining Islamic civilization. The results of the analysis of various sources of literature also resulted in the classification of the flow of events and cause-and-effect of the colonization of the West against Islamic civilization from various aspects. After experiencing colonization by the West, Muslims began to show various responses that led Islam into a new period called the modern period, marked by the emergence of renewal. The results of the analysis of various sources of literature also resulted in the classification of the flow of events and cause-and-effect of the occurrence of Muslim responses to the colonization of the West from various sides.